Functional capacity in a rat model of heart failure: impact of myocardial infarct size. Issue 11 (1st November 2017) - Hentschke, Vítor Scotta; Capalonga, Lucas; Rossato, Douglas Dalcin; Perini, Júlia Luíza; Alves, Jadson Pereira; Quagliotto, Edson; Stefani, Giuseppe Potrick; Karsten, Marlus; Pontes, Mauro; Dal Lago, Pedro
Abstract : New Findings: What is the central question of this study? To the best of our knowledge, no studies have evaluated oxygen uptake, carbon dioxide production and exercise tolerance in rats that have undergone myocardial infarction classified by myocardial infarct (MI) size. What is the main finding and its importance? Oxygen uptake and exercise intolerance are MI size dependent, and classification based on MI size can distinguish rats with functional capacity impairment. Rats with a large MI (>40% of the left ventricle) might provide a good model for the testing of new therapies that have the potential to modify the variables of functional capacity. Oxygen uptake ( V ̇ O 2 ) and exercise tolerance in rats classified by myocardial infarct (MI) size are underexplored. The aim of this study was to evaluate V ̇ O 2, carbon dioxide production ( V ̇ C O 2 ) and exercise tolerance in rats that had undergone myocardial infarction. Fourteen weeks after myocardial infarction or sham surgery, rats underwent an integrated approach to evaluation of left ventricular function and V ̇ O 2 / V ̇ O 2 V ̇ C O 2 V ̇ C O 2, exercise tolerance and skeletal muscle weight. Based on determination of MI size, rats were assigned to sham‐operated controls (Sham, n  = 12), small myocardial infarction (SMI, n  = 8) and large myocardial infarction (LMI, n  = 5) groups. The LMI rats showed lower systolic (ejection fraction and fractional shortening) and diastolic (E/A ratio) left ventricular function compared with SMI. Maximal V ̇ O 2 (∼24%, P  < 0.05), V ̇ O 2 reserve (∼30%, P  < 0.05), time to exhaustion (∼36%, P  < 0.05) and maximal velocity (∼30%, P  < 0.05) were lower in LMI compared with sham‐operated control animals, with no difference between SMI rats and sham‐operated controls. Maximal V ̇ C O 2 and respiratory exchange ratio showed no significant difference between MI rats and sham‐operated control rats. The LMI rats demonstrated lower gastrocnemius weight (∼12%, P  < 0.05) and soleus weight (∼19%, P  = 0.07) compared with sham‐operated control rats. Significant correlations between MI size, left ventricular end‐diastolic pressure, right ventricle hypertrophy, pulmonary congestion, ejection fraction and fractional shortening with maximal V ̇ O 2 and distance run were observed. Oxygen uptake and exercise intolerance are MI size dependent. Abstract :